Pengembangan Lembar Kerja Peserta Didik Berbasis Guided Inquiry untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Ananda, Chandrini Faiza; Tanjung, Indayana Febriani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The development of guided inquiry-based worksheets is based on the lack of learning media in high school biology subjects that can help students think critically. The aim is to develop LKPD based on guided inquiry that is feasible, effective, and practical to help students improve their critical thinking skills. The method is the R&D model of Thiagarajan et al. (1974) namely 4D design, including: define, design, develop, and disseminate. The data analysis technique used is quantitative and qualitative. Quantitative data analysis is used to see the level of feasibility, practicality, and effectiveness. Meanwhile, qualitative data analysis is to find out comments, criticisms, suggestions, and observations. It was found that the guided inquiry-based LKPD that had been developed was feasible to be applied with a percentage of 100% (media expert), 89% (material expert), and 100% (language expert), and the LKPD was declared practical as seen from the achievement of the teacher response sheet with an average 100% and student response sheets with an average of 93.07%. LKPD was also declared effective as seen from the achievement of post-test completeness of 0.70 in the medium category. Based on the results above, it can be concluded that the guided inquiry-based worksheets that have been developed are declared feasible, practical, and effective to use, and can improve students' critical thinking skills.